ASSESSMENT OF SOIL PROPERTIES AS AFFECTED BY FOUR LAND USE TYPES IN EGBEADA, SOUTH - EAST NIGERIA - Donald Nweze OSUJIEKE; Juliet Nnenna IGBOJIONU; Pedro Ezemon IMADOJEMU; Jude Nnanyere IROHA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study was conducted to ascertain the influence of four land use types [plantain plantation (PP), cassava farm (CF), whistling pine forest (WPF) and fallow land (FL)] on soil properties of Egbeada in South-east, Nigeria. Stratified sampling technique was used in the collection of soil samples from the land-uses. Composite samples were collected from each land-use for routine and selected special laboratory analyses. Data generated were analyzed statistically using analysis of variance. Sand particles had a mean of 85.20 %, 85.80 %, 83.60 % and 78.80 % for soils under PP, CF, WPF, and FL, respectively. The pH(H2O) had mean of 6.35, 6.42, 5.36 and 5.81 soils under PP, CF, WPF, and FL while organic matter had mean of 2.94 % for PP and FL, 1.47 % for CF and 2.79 % for WPF. However, available Zn of the studied soils had mean of 8.7 mg kg-1, 6.8 mg kg-1, 5.3 mg kg-1 and 4.9 mg kg-1 in decreasing order of fallow land > whistling pine forest > plantain plantation > cassava farm, respectively. The organic matter under soils of cassava farm differed significantly (P = 0.05) with that of plantain plantation, whistling pine forest, and fallow land. The available Zn and Cu differed non-significantly among soils of the various land-uses. However, the result obtained from the study indicated that the different land-uses have affected the soils at a various rate.